EFEKTIVITAS MEDIA SCRAPBOOK DALAM PEMBELAJARAN KETERAMPILAN MEMBUAT ONDE ONDE BAGI SISWA DISABILITAS INTELEKTUAL DI SEKOLAH LUAR BIASA - Rizka Oktavia; Setia Budi; Zulmiyetri; Johandri Taufan; Mardatillah Zulpiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research os motivates by the problems found in SLB 1 Bukittinggi namely a class X SMALB intellectual disability student whose achievement in culluary vocational skills is not optimal. This study aims to determine the effectiveness of scrapbook media in optimizing culinary vocational skills in students eith intellectual disabilities. This study uses an experimental method eith a single subject research approach by implementing an A-B-A design. Data analysis is carried out with a visual approach presented through graphics, and techniques in data collection through observation accompanied by practice. Data obtained from the analysis of 12 meetings devided into 3 phases, namely basaline (A1), intervention (B), end basaline (A2). The results of this study in the (A1) basaline phase obtained a percentage of 41% rith 3 meetings. Furthermore , durinf the intervention phase there wa an increase in ability with a percentage of 61%, 83%, 85% 90% 90% 90% with 6 meetings after which the intervanetion was stopped. Followe by basaline (A2) whict yielded a 100% percentage result in there obersations. Thus, it cam be councluded that scarpbokk media can provide a positive contribution to improvinf the abilities of students with intellectual disabilities in learning culinary vocational skills.